Distribution and Population Status of Bald Eagles (Haliaeetus leucocephalus) in Interior Alaska - Ritchie, Robert J.; Ambrose, Skip (ARCTIC, 1996)
We summarize information available on natural history, numbers, distribution, and status of bald eagles (Haliaeetus leucocephalus) in six regions of interior Alaska: Upper Yukon, Lower Yukon, Tanana, Kuskokwim, Susitna, and Upper Copper. We identified 347 nesting territories using information from local researchers, a raptor nest atlas, unpublished raptor survey reports, and our own surveys. Nearly 85% of these territories were from the Copper, Susitna, and Tanana drainages. Extrapolating from the number of known nests and approximate survey coverage per drainage, we estimate that 525 to 725 pairs of bald eagles nest in interior Alaska. Observations also suggest that this population has increased substantially since the middle fo this century and that numbers in some areas continue to increase. Reasons for these increases may include (1) improving health of individuals in this population; (2) reduced persecution in Alaska and in wintering areas outside the state; (3) immigration into interior Alaska from rebounding or expanding populations elsewhere; and (4) changing environmental conditions (e.g., warmer temperatures). Banding and migration data suggest that part of the population that nests north of the Alaska Range may winter in areas different from those used by populations that nest south of the Alaska Range. No environmental contaminants measured in eggs occurred at concentrations known to result in sublethal or lethal effects, and most organochlorine pesticide and mercury concentrations were an order of magnitude lower than concentrations in bald eagle eggs elsewhere in the United States. On fait la synthèse de l'information disponible sur l'histoire naturelle, l'inventaire, la distribution et le statut du pygargue à tête blanche (Haliaeetus leucocephalus) dans six régions de l'intérieur de l'Alaska: le Haut-Yukon, le Bas-Yukon, la Tanana, la Kuskokwim, la Copper supérieure et la Susitna. En utilisant l'information obtenue auprès de chercheurs locaux, un atlas sur les nids de rapaces, des rapports ...